2014
DOI: 10.1007/s13197-014-1502-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing antioxidant activity, microbial and sensory quality of mango (Mangifera indica L.) juice by γ-irradiation and its in vitro radioprotective potential

Abstract: Gamma irradiation is an effective method currently being used for microbial decontamination and insect disinfestations of foods. In the present study, mango (Mangifera indica L.) juice was irradiated at doses of 0, 1.0, 3.0 and 5.0 kGy and microbial load, total polyphenols, flavonoids, ascorbic acid content, antioxidant activities, colour and sensory properties were evaluated immediately after irradiation and also during storage. Microbiological assay of the fresh and stored mango juice showed better quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 42 publications
2
7
2
1
Order By: Relevance
“…Earlier studies elsewhere show that irradiation from 1 to 10 kGy can be effective to reduce spoilage and pathogenic micro-organisms in food, and the dose above 3 kGy can inactivate mold, yeast and bacteria (Stefanova et al 2010). It is also reported that irradiation at 3 to 5 kGy can completely inactivate mold and bacteria (Naresh et al 2015). Our results agree well with these reported results to inhibit microbial contamination at low irradiation doses.…”
Section: Irradiation Dosessupporting
confidence: 93%
See 3 more Smart Citations
“…Earlier studies elsewhere show that irradiation from 1 to 10 kGy can be effective to reduce spoilage and pathogenic micro-organisms in food, and the dose above 3 kGy can inactivate mold, yeast and bacteria (Stefanova et al 2010). It is also reported that irradiation at 3 to 5 kGy can completely inactivate mold and bacteria (Naresh et al 2015). Our results agree well with these reported results to inhibit microbial contamination at low irradiation doses.…”
Section: Irradiation Dosessupporting
confidence: 93%
“…Therefore, proper level of flavonoids in the fermentation substrate may favour the production of some enzymes. Compared with autoclaved substrate, irradiated substrate had higher level of flavonoids (Figure 4c) that agrees well with previous studies (Naresh et al 2015). Therefore, fungal fermentation on irradiated substrate produced more enzymes.…”
Section: Comparison Of Substrate Components Right After Treatmentsupporting
confidence: 91%
See 2 more Smart Citations
“…The contemporary findings have been reported by Harrison & Were (2007), who showed that the rise of date fruits phenolic content should be given to their launch from glycosidic precursors and the degradation of bigger polymeric phenolic compound to lower gadgets through gamma-ray treatments. Furthermore, Naresh, Varakumar, Variyar, Sharma, & Sarathi Reddy (2015) indicated that the degradation of conjugated phenolic compounds should define the higher phenolic content in gamma-irradiated date samples. In the same concern Aly, Maraei, & Ali (2016) found that phenolic and flavonoids were significantly expanded by expanding irradiation dose levels of Egyptian Moringa oleifera seed oils.…”
Section: Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 99%